RECESSIVE LETHALS: A NEW CLASS OF NONSENSE SUPPRESSORS IN Escherichia coli - Soll, Larry (1969)
Two new nonsense suppressors in Escherichia coli were found in partial diploids carrying F′14 and were shown to be on the episome. These suppressors can exist only in cells which also contain the su(-) allele, i.e., su(+)/su(-) heterozygotes. Presumably the mutations cause an alteration of an essential cellular component, the complete loss of which is lethal. Su7, an amber suppressor, has an efficiency of 76 per cent and su8, an ochre suppressor, an efficiency of 4 per cent.